2017
DOI: 10.1038/s41598-017-16189-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gut microbiome and plasma short-chain fatty acid profiles in a spontaneous mouse model of metabolic syndrome

Abstract: Male Tsumura Suzuki obese diabetes (TSOD) mice spontaneously develop obesity and obesity-related metabolic syndrome. Gut dysbiosis, an imbalance of gut microbiota, has been implicated in the pathogenesis of metabolic syndrome, but its mechanisms are unknown. Short-chain fatty acids (SCFAs) are the main fermentation products of gut microbiota and a link between the gut microbiota and the host’s physiology. Here, we investigated a correlation among gut dysbiosis, SCFAs, and metabolic syndrome in TSOD mice. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 91 publications
3
62
1
Order By: Relevance
“…These data are partly consistent with a previous report of Nishitsuji et al demonstrating that not only a trend to increase in the ratio of Firmicutes to Bacteroidetes (Fig. S6), but also the ratio was significantly lower in mice that develop obesity-diabetes syndrome [16]. Despite LF mice exhibiting less body weight gain than HF mice, the lower ratio observed in the LF group is likely the consequence of a low-fat purified diet being used, contributing to lower levels of acetate in particular.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are partly consistent with a previous report of Nishitsuji et al demonstrating that not only a trend to increase in the ratio of Firmicutes to Bacteroidetes (Fig. S6), but also the ratio was significantly lower in mice that develop obesity-diabetes syndrome [16]. Despite LF mice exhibiting less body weight gain than HF mice, the lower ratio observed in the LF group is likely the consequence of a low-fat purified diet being used, contributing to lower levels of acetate in particular.…”
Section: Discussionsupporting
confidence: 93%
“…This genus also was found to negatively correlate with plasma TG levels in a large, recent cohort study [34]. Moreover, in both HF-EVOO and HF-FO mice, a significant elevation of bacteria from Allobaculum and Coriobacteriaceae, which are associated with lean phenotype [16], was observed in comparison with HF mice. It should be noted that mice-fed HF-FO showed a significantly higher abundance of bacteria from the Unclassified clostridiales genera in comparison with LF, HF, and HF-EVOO.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent study revealed that gut dysbiosis in Tsumura Suzuki obese diabetes (TSOD) mice leads to a reduction in total plasma SCFA levels, where acetate was decreased, with an increase in propionate and butyrate, while valerate and hexanoate were absent in the TSOD mice compared with controls (Nishitsuji et al . ). In aquatic animals such as Atlantic salmon ( Salmo salar ) and Atlantic cod ( Gadus morhua ), supplementation with soybean‐derived protein (Ringø et al .…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 97%
“…Furthermore, stress-stimulated microbiota dysbiosis may be a factor influencing the production of SCFA in the gut. A recent study revealed that gut dysbiosis in Tsumura Suzuki obese diabetes (TSOD) mice leads to a reduction in total plasma SCFA levels, where acetate was decreased, with an increase in propionate and butyrate, while valerate and hexanoate were absent in the TSOD mice compared with controls (Nishitsuji et al 2017). In aquatic animals such as Atlantic salmon (Salmo salar) and Atlantic cod (Gadus morhua), supplementation with soybean-derived protein (Ringø et al 2006;Green et al 2013) as well as in largemouth bronze gudgeon (Coreius guichenoti) and grass carp, which suffer from infections (Li et al 2016;Tran et al 2018), resulted in significant changes in gut microbiota.…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 99%